Women and Inheritance in Nineteenth-Century Newfoundland - Johnson, Trudi (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2002)
AbstractThis paper tests the idea that concepts of property in English common law favoured male heirs in the primogeniture system of land inheritance and disadvantaged women upon marriage. A case study of wills in nineteenth-century Newfoundland demonstrates that instead of strict adherence to centuries of common-law tradition, both men and women in Newfoundland were more concerned with the support and maintenance of the family under the unique conditions of the Newfoundland economy. The male line of descent was subordinated to the immediate and long-term needs of the family through more egalitarian inheritance practices. These practices in tum sustained a mat rimonial property system that well pre-dated legislation to protect married women's property.